Radiation-induced dose-dependent changes of the spleen following postoperative chemoradiotherapy for gastric cancer. Issue 2 (August 2015) - Trip, Anouk Kirsten; Sikorska, Karolina; van Sandick, Johanna W.; Heeg, Maarten; Cats, Annemieke; Boot, Henk; Jansen, Edwin Petrus Marianus; Verheij, Marcel
Abstract: Background and purpose: Abdominal (chemo-)radiotherapy is associated with dose-limiting toxicity of various normal structures. The purpose of this retrospective study was to investigate radiation-induced changes of the spleen and their clinical consequences. Patients and methods: In gastric cancer patients treated with postoperative chemoradiotherapy, the spleen size and its functions were assessed at follow-up by spleen volume on CT-scan, serum leucocytes/thrombocytes, and the occurrence of infectious events consisting of pneumonia and fatal sepsis. To evaluate the effect of radiation dose, mixed effects and Cox regression models were used. Results: Forty-six out of 90 consecutive patients treated from 2006 to 2011 were evaluable. All patients received 45 Gy in 25 fractions with concurrent capecitabine ( n  = 8), and capecitabine/cisplatin ( n  = 38). Median Dmean to the spleen was 40 Gy (range 32–46). Mean relative spleen volume reduced to 37% (95% CI 32–42%) at 4-year follow-up, which was most strongly associated to the V44 ( p  < 0.001). Median follow-up time was 67 (95% CI 57–78) months. Eleven patients had 13 pneumonias and 3 fatal sepsis. No association with dosimetric parameters was observed. Conclusions: In postoperative chemoradiotherapy for gastric cancer, the spleen received a high radiation dose. This resulted in a progressive, radiation dose-dependent reduction of spleen volume. Pneumonia and fatal sepsis occurred frequently, possibly as a result of functional hyposplenia.